Posterior Cervical Intramuscular Schwannoma Within the Trapezius Muscle: A Case Report - Naoto Koike; Hisashi Hasegawa; Hiroumi Matsuzaki; Takeshi Oshima (Turkish Archives of Otorhinolaryngology, 2022)

(untitled)
Schwannomas are benign soft tissue tumors derived from the Schwann cells of the peripheral nerves. An intramuscular schwannoma arising within the trapezius muscle in the posterior neck is rare. We report a case of a 31-year-old woman with an intramuscular schwannoma in the trapezius muscle. A painless and smooth-surfaced mass from 10 years ago was evident on palpation in the right posterior neck. Ultrasonography revealed an oval mass with clear borders and slight internal blood flow. No continuous hypoechoic lesions were noted at the tip of the mass. Magnetic resonance imaging of the neck revealed a mass in the right posterior cervical trapezius muscle with isointensity on T1-weighted imaging and heterointensity on T2-weighted imaging. Based on these findings, a schwannoma was suspected. Ultrasonography guided fine needle aspiration cytology revealed no significant findings. During surgery, a white-colored, encapsulated-tumor mass was found in the trapezius muscle. Histopathologically, hypocellular and hypercellular areas of fusiform cells were conspicuous, and nuclear palisading was observed in a part of the hypercellular region, confirming the diagnosis of schwannoma. To our knowledge, this is an extremely rare report of an intramuscular schwannoma within the trapezius muscle; herein, we report its clinical, radiological, and pathological features.